Sensorless control of switched reluctance motor based on full-cycle inductance space vector - ZHANG Xulong; WANG Feng; CAO Yanjing; SHAO Xiaogen (Gong-kuang zidonghua, 2014)
In view of problems of less reliability and more complexity of switched reluctance motor caused by rotor position sensor, a sensorless control method of switched reluctance motor based on full-cycle inductance space vector was proposed. In the method, each phase is injected with drive pulse at starting stage of the motor, non-conducting phase is injected with driving pulse and conducting phase uses energy returnable current chop control at running stage of the motor, so as to identify full-cycle inductance by calculating current slope difference. Then, the rotor position is estimated through relationship between full-cycle inductance space vector and its angle. The simulation and experimental results show that the maximum estimation errors of the rotor position at starting and steady running stage of the motor are 0.8° and 0.5° respectively, which meet accuracy requirement of sensorless control of switched reluctance motor.